Intellectual Property Animasi Di Indonesia Dalam Buku Katalog Nganimasi Indonesia - Bambang Gunawan Santoso (Jurnal Bahasa Rupa, 2018)
IP or Intellectual Property refers to the creation of the mind; invention; literary and artistic works; symbols, names and drawings used in the trade. Intellectual property rights (HKI) are rights granted to IP creators, and include trademarks, copyrights, patents, industrial design rights, and in some trade secret jurisdictions. Works of art including music and literature, as well as discoveries, words, phrases, symbols and designs can all be protected as intellectual property or IP. Until now the catalog book "IP Animasi Indonesia" does not exist yet; while other countries such as Korea have released an annual catalog of animations since 2005. (The author data when he got 6 months internship scholarship at KOCCA - Korea Creative Content Agency in 2008, and a special invitation to Korea in November 2015). So through the process of collecting data with the method of collecting data periodically (time series) for more than 1.5 years, the author ventured to collect the work of colleagues from almost all of Indonesia. Once collected, the data is sorted, tidied up, rearranged, and then compiled in a book entitled NGANIMASI INDONESIA: Indonesia Animation Industry Data (NI). The results of this study revealed that until August 2017 there were 56 IPs categorized in animation character collected. 64% of the 56 IPs are character designs of humans or people; while the remaining 36% are animals, objects, and custom characters.